Family members' perspective of family Resilience's risk factors in taking care of schizophrenia patients - Rizki Fitryasari; Ah Yusuf; Nursalam; Rr Dian Tristiana; Hanik Endang Nihayati (Elsevier, 2018)
Objectives: The study was conducted to illustrate the risk factors of family resilience when taking care of patients with schizophrenia. Methods: The research used qualitative design with an interpretive phenomenology approach, with in-depth interviews. The subjects were 15 family members who cared for patients with schizophrenia at the Menur Mental Hospital, Surabaya, Indonesia. The samples were obtained by purposive sampling technique. The data was collected by interview and using field notes, then analyzed by Collaizi technique. Results: This research produced two themes, they were care burden and stigma. Care burdens felt by families were confusion about the illness, emotional, physical, time, financial and social burdens, which leads to decrease in family quality of life. Families also experienced stigma called labeling, stereotyping, separation and discrimination. Stigmas meant that families faced psychological, social and intrapersonal consequences. This decreased the family quality of life and functionality of the family, and there were opportunities for negative results to family resilience. Health workers, especially psychiatric nurses, should review care burdens and stigma to develop nursing interventions so families are able to achieve resilience. Conclusions: This research explained how care burden and stigma are risk factors that must be managed by families to survive, rise up, and become better in caring for patients with schizophrenia. Nurses have a central role in assessing the level of care burdens and stigma in order to help families achieve resilience. Further research may focus on family-based nursing interventions to lower care burden, and community-based interventions to reduce stigma. Keywords: Family, Indonesia, Psychiatric nursing, Resilience, Psychological, Risk factors, Schizophrenia